Progressive Muscle Relaxation on Depression Levels in Schizophrenia Patients Treated in Griya Medika - Pratiwi, Ayu; Edmaningsih, Yunike; Ramadhan , Ahmad Farid; Hapsari, Fahira Noviantika Dwi (Sarana Ilmu Indonesia (salnesia), 2025)
Patients with schizophrenia often exhibited behaviors such as social withdrawal, hypervigilance, difficulty in management, and vulnerability to anxiety and depression. Progressive Muscle Relaxation (PMR), as a muscle relaxation technique, had been shown in stress management programs to alleviate symptoms of anxiety, depression, and insomnia. The purpose of this study was to examine the effect of Progressive Muscle Relaxation (PMR) on depression levels among patients with schizophrenia at Panti Griya Medika. This study employed a quasi-experimental design using a pretest–posttest without a control group approach. The sample consisted of 30 subjects, selected through purposive sampling. Data were collected using a demographic questionnaire and the Hamilton Depression Rating Scale (HDRS), which consists of 17 items to assess the severity of depression. Data analysis was conducted using the paired t-test. Clinically, there was a decrease in depression scores by 2.1 points following the administration of PMR. However, statistically, this reduction from 12.20 to 10.10 did not show a significant effect; therefore, the effectiveness of PMR therapy in reducing depression in schizophrenia patients could not be strongly validated through this study. It is therefore recommended that PMR be implemented regularly as a complementary non-pharmacological intervention in the management of depression among patients with schizophrenia.